2001
DOI: 10.1074/jbc.m008073200
|View full text |Cite
|
Sign up to set email alerts
|

C-Mannosylation and O-Fucosylation of the Thrombospondin Type 1 Module

Abstract: Thrombospondin-1 (TSP-1) is a multidomain protein that has been implicated in cell adhesion, motility, and growth. Some of these functions have been localized to the three thrombospondin type 1 repeats (TSRs), modules of ϳ60 amino acids in length with conserved Cys and Trp residues. The Trp residues occur in WXXW patterns, which are the recognition motifs for protein C-mannosylation. This modification involves the attachment of an ␣-mannosyl residue to the C-2 atom of the first tryptophan. Analysis of human pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
228
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(239 citation statements)
references
References 60 publications
10
228
0
1
Order By: Relevance
“…Recently the presence of O-fucose in a different protein context was reported (27). Hofsteenge and co-workers showed the presence of the disaccharide Glc-Fuc O-linked to serines and threonines within the three thrombospondin type 1 repeats (TSR) of human thrombospondin-1.…”
Section: Figmentioning
confidence: 99%
“…Recently the presence of O-fucose in a different protein context was reported (27). Hofsteenge and co-workers showed the presence of the disaccharide Glc-Fuc O-linked to serines and threonines within the three thrombospondin type 1 repeats (TSR) of human thrombospondin-1.…”
Section: Figmentioning
confidence: 99%
“…Functions associated with the TSRs found in THBS-1 include cell attachment, angiogenesis inhibition, protein-protein interactions, and protein-glycosaminoglycan interactions [12]. The module is subject to two unusual carbohydrate modifications, introduction of a mannose onto a conserved tryptophan, and of a fucose-glucose onto a conserved serine or threonine [21] (Fig. 2D).…”
Section: Thrombospondin Type 1 Repeats Overviewmentioning
confidence: 99%
“…Two fucose moieties were bound to the complex at Thr432 and Thr489. Predicted C-mannosylation was not observed, as the S2 cell expression system is incapable of this modification [19,21]. However, it was observed that the Cδ1 atoms of the predicted tryptophan modification sites are exposed in the structure.…”
Section: Thbs-1 Tsr2-tsr3 Crystal Structurementioning
confidence: 99%
See 2 more Smart Citations